Comparative Analysis of Lumpsum Contract and Unit Price Contract Risk Using Analytical Hierarchy Process Method: Case Study of Contractors in Bekasi - Anjas, Handayani; Tiara, Irma (NAROTAMA UNIVERSITY, Indonesia, 2020)
Bekasi Regency Government gives priority in infrastructure development. According to the Central Statistics Agency for West Java Province, the population of Bekasi was 2,344,871 people in 2018. The Bekasi Regency Government will build roads in 28 locations, one of which is to improve the existing infrastructure in Bekasi. In every business, there will always appear two contradictory things which are profit and profit, including in the construction services business. Construction activities can be completed when meeting all the objectives that have been set, following the agreed costs, and meet the quality that has been previously agreed upon. The purpose of this study is to study agreements regarding lump-sum contracts and unit price contracts. This research method uses the Analytical Hierarchy Process Method. The research process starts with creating problems and making hierarchical arrangements. The hierarchical structure consists of three things namely objectives (level I), criteria (level II), and alternatives (level III). Once organized, the hierarchy will be attended by using a questionnaire for 30 respondents. After the data is obtained, the data is tabulated, then the paired frame is searched, move in pairs, and the priority weights. The results of the analysis by the AHP method were obtained in a construction project in Bekasi City, the factor of using Lumpsum contract was more influential compared to the contract Unit price with a ratio of 52.01%: 47.99%.